Ziziphus Jujube: a review study of its anticancer effects in various tumor models invitro and invivo - Ebrahimi, S.; Mollaei, H.; Hoshyar, R. (Cellular and Molecular Biology, 2017)
The growing rate of cancer incidences and inefficiency of current therapies have made scientists to find novel agents such as medicinal plants. Ziziphus jujube is one of these plants whose pharmaceutical effects have been studied for a long time. Recent investigations have proved that bioactive compounds of Ziziphus jujube including triterpenic acids, flavonoids, cerebrosides, phenolic acids, Î± tocopherol, Î² carotene, and polysaccharides have anti-proliferative effects on several cancerous cell lines and animals. The present study aimed to cover all previous invitro and invivo findings and some of molecular mechanisms of its anticancer property.